THE ROLE OF PSYCHOLOGICAL CAPITAL IN GOVERNMENT ORGANIZATION PERFORMANCE SUSTAINABILITY - Suhariadi, Fendy; Wijoyo, Suparto; Sinaga, Eduard; Indaryanto, Adrid; Harijadi, Bambang (Department of Government, FISIP, Universitas Padjadjaran, 2024)
Every government organization's Basic and natural goal is to maintain sustainability from generation to generation. One of the important things that impact the sustainability of a government organization is the psychological capital. A good relationship, independently or together, between self-efficacy, resilience, optimism, and hope has been proven to influence Growth, Development, and Productivity as advances for the Government Organization. A person with good psychological capital is assumed to be able to provide maximum effort and produce creative behavior to achieve set goals. This study aims to identify the role of psychological capital in the economic sustainability of government Organizations. This study uses a quantitative approach with an explanatory study design. The results of this study found that self-efficacy has a vital role in determining the economic sustainability of government Organizations, causing a more significant increase in the economic sustainability of government Organizations compared to self-efficacy; moderation of hope plays a vital role in increasing the influence of self-efficacy on economic sustainability and optimism which functions as a moderating variable that increases the impact of resilience on the economic sustainability of government Organization substantially.gb777